Immune and behavioral correlates of protection against symptomatic post-vaccination SARS-CoV-2 infection - Goguet, Emilie; Olsen, Cara H.; Meyer, William A.; Ansari, Sara; Powers, John H.; Conner, Tonia L.; Coggins, Si’Ana A.; Wang, Wei; Wang, Richard; Illinik, Luca; Sanchez Edwards, Margaret; Jackson-Thompson, Belinda M.; et al. (Frontiers in Immunology, 2024)
We sought to determine pre-infection correlates of protection against SARS-CoV-2 post-vaccine infections (PVI) acquired during the first Omicron wave in the United States. Serum and saliva samples from 176 vaccinated adults were collected from October to December of 2021, immediately before the Omicron wave, and assessed for SARS-CoV-2 Spike-specific IgG and IgA binding antibodies (bAb). Sera were also assessed for bAb using commercial assays, and for neutralization activity against several SARS-CoV-2 variants. PVI duration and severity, as well as risk and precautionary behaviors, were assessed by questionnaires. Serum anti-Spike IgG levels assessed by research assay, neutralization titers against Omicron subvariants, and low home risk scores correlated with protection against PVIs after multivariable regression analysis. Commercial assays did not perform as well as research assay, likely due to their lower dynamic range. In the 32 participants that developed PVI, anti-Spike IgG bAbs correlated with lower disease severity and shorter duration of illness.